Efeito do pH, relação DQO/Sulfato e fonte de carbono na biorremediação de drenagem ácida de minas sob condições ácidas em reator UASB - Acerbi, Karl Wagner (2015)
This work consisted in an evaluation of an UASB reactor treating synthetic acid mine drainage by different operation strategies. Two identical reactors were tested, wherein their operation were differentiated by the carbon source, using ethanol – RE and lactate – RL. The variations were: affluent pH, varying from 3.0 (phase I), to 3.5 (phase II) and 4.0 (phase III) and in the COD/Sulfate ratio, being 2.0 in the three initials phases and reduced by COD variation to 1.5 (phase IV) and 0.8 (phase V). For RE pH changes didn’t cause big variations, wherein the average values of phases I, II and III are: effluent pH 5.03, COD removal 34%, sulfate removal 88%, production of sulfide 122 mg/L, alkalinity 101 mg/L, acetic acid 127.7 mg/L and H2S 1.5 E-03 mol/L. The COD reduction caused a lower SRB activity in RE, which average removal went from 87% (phase III) to 58% (phase V), production of sulfide from 119 to 55 mg/L, alkalinity from 105 to 38 mg/L, acetic acid from 116 to 73 mg/L and H2S from 1.2 E-03 to 4.1 E-04 mol/L. The COD removal, however, present a increase from 29 to 48%, indicating that another group, other than SRB, started to consumption ethanol. There was no significant variation of effluent pH on last phases because the system was buffered by acetic acid. For RL the modifications had a positive or neutral, statistically speaking, impact, since on phase I there was no SRB activity due prevalence of the lactic acid in very acid pH. The modifications to the other phases (II, III, IV and V), had, respectively, the following averages results: pH: 4.6, 6.44, 7.15 and 7.66; COD removal: 19, 33, 46 and 54%; sulfate removal: 58, 70, 90 and 84%; sulfide: 67, 87, 127 and 124 ug/L; alkalinity: 101, 266, 287 e 225 mg/L; acetic acid: 55.7, 129.8, 127.7 and 34.1 mg/L. The H2S concentrations are influenced by pH on the concentration form phase, being: 9.0 E-04, 6.7 E-03 and 8.9 E-04, in which the “pulse” observed in phase III was due to pH.